Eating disorders and cardiovascular outcomes: Protocol for a systematic review (Research, Society and Development, 2023)
Eating disorders, defined as: Pica, rumination, restrictive/avoidance eating, anorexia nervosa, bulimia nervosa, binge eating and other specified eating disorders, are psychiatric conditions and feature disordered eating behavior, not the attitude of individuals towards it. to weight, as well as their perception of body shape, is disturbed. This study aims to present the development of a systematic literature review protocol that aims to verify whether there is an association between eating disorders and all-cause mortality, thus whether eating disorders are risk factors for cardiovascular events. The study will be carried out following the recommendations of the Cochrane Collaboration and will be reported in accordance with the Guideline “Moose Guidelines for Meta-Analyses and Systematic Reviews of Observational Studies. As the study is based on documentary documents, ethics approval is not required. The results of the systematic review will be presented at various conferences and will be published in a peer-reviewed journal. The protocol is published in PROSPERO under registration number CRD42022358832. Finally, with this study, in addition to advancing scientific knowledge in the area, it is expected to know more and better about this sphere, seeking greater longevity and better quality of life, in addition to reducing fatal outcomes related to eating disorders and heart conditions, such as also reducing costs to the healthcare system.